Pemikiran Agustinus tentang Dosa dalam Terang 1 Yohanes 2:16: Sebuah Kajian atas Kejatuhan Manusia - Sitinjak, Ferdinand; Prasetyo, Edhi; Ongirwalu, Epifana; Amtiran, Abdon (Metta : Jurnal Ilmu Multidisiplin, 2025)
Augustine's thinking on sin is one of the pillars of Christian theology, but it is often narrowed down to merely a moral transgression, rather than the existential condition of humanity after the Fall. In the modern context, marked by materialism and an increase in the intensity of worldly desires, this theological understanding needs to be re-examined. This study aims to analyze the relationship between Augustine's theological anthropology and the classification of three forms of sin in 1 John 2:16: the lust of the flesh, the lust of the eyes, and the pride of life. Using a theological-hermeneutic qualitative analysis of patristic and biblical theology literature, this study presents a hermeneutic integration between Augustine's theology and John's hamartology. The results show that Augustine understands sin as misdirected love, namely the reversal of the human heart from God toward oneself (incurvatus in se), in line with the description of epithumia in 1 John. This study concludes that sin is an existential corruption of human nature manifested through disordered love. The novelty of this study lies in its integrative explanation of the relationship between Augustine's ordo amoris and the three categories of desire in 1 John 2:16, which enriches the theological understanding of the existential nature of sin in contemporary theological discourse.